2016
DOI: 10.1038/srep22177
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the assassin’s arms: insights from a phylogeny of combined transcriptomic and ribosomal DNA data (Heteroptera: Reduvioidea)

Abstract: Assassin bugs (Reduvioidea) are one of the most diverse (>7,000 spp.) lineages of predatory animals and have evolved an astounding diversity of raptorial leg modifications for handling prey. The evolution of these modifications is not well understood due to the lack of a robust phylogeny, especially at deeper nodes. We here utilize refined data from transcriptomes (370 loci) to stabilize the backbone phylogeny of Reduvioidea, revealing the position of major clades (e.g., the Chagas disease vectors Triatominae)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
64
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(84 citation statements)
references
References 48 publications
11
64
1
1
Order By: Relevance
“…Previous phylogenetic hypotheses across Reduviidae (Weirauch, ; Weirauch & Munro, ; Hwang & Weirauch, ; Zhang et al ., ) supported the clade we recognize here as the subfamily Ectrichodiinae sensu n. (including Tribelocephalinae), which was also well supported in all of our current analyses. In contrast, these earlier analyses lacked adequate taxon and character sampling to reconstruct relationships within Ectrichodiinae sensu n. , specifically testing the hypotheses that the two former subfamilies, Ectrichodiinae and Tribelocephalinae, are not reciprocally monophyletic [Weirauch & Munro, (in part); Weirauch, ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Previous phylogenetic hypotheses across Reduviidae (Weirauch, ; Weirauch & Munro, ; Hwang & Weirauch, ; Zhang et al ., ) supported the clade we recognize here as the subfamily Ectrichodiinae sensu n. (including Tribelocephalinae), which was also well supported in all of our current analyses. In contrast, these earlier analyses lacked adequate taxon and character sampling to reconstruct relationships within Ectrichodiinae sensu n. , specifically testing the hypotheses that the two former subfamilies, Ectrichodiinae and Tribelocephalinae, are not reciprocally monophyletic [Weirauch & Munro, (in part); Weirauch, ].…”
Section: Discussionsupporting
confidence: 85%
“…Despite the diversity of sexually dimorphic characters and the size of the group, which make Ectrichodiinae a compelling study system, investigations into the evolution of sexual dimorphism are currently impeded by a lack of comprehensive phylogenetic hypotheses for this group. Recent morphological and molecular phylogenetic or phylogenomic analyses of Reduviidae incorporated few representatives of Ectrichodiinae (Weirauch, , ; Weirauch & Munro, ; Hwang & Weirauch, ; Zhang et al ., ), except for a combined morphological and molecular analysis that focused on Madagascan Ectrichodiinae (Forthman & Weirauch, ). These studies support Ectrichodiinae (or part thereof; see later) as the sister taxon to Tribelocephalinae, a moderate‐sized subfamily (150 species, 16 genera) that comprises mostly cryptically coloured species that display little sexual dimorphism (Maldonado, , ; Rédei, ; Weirauch, ; Ishikawa et al ., ; Davranoglou, ; Weirauch et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of a higher diversity of the species closely related to Triatominae and its tribes Alberproseniini, Bolboderini and Cavernicolini, and the use different analytical approaches (such as investigating metabolic pathways or transcriptomes [31]) will give better insights into the evolution of blood feeding.…”
Section: Triatominae Monophyly Vs Paraphylymentioning
confidence: 99%
“…Furthermore, for some taxonomic groups, phylogenomic approaches have been developed and improved for application to material that has historically been difficult to use with Sanger sequencing approaches (e.g., historical museum samples with highly degraded DNA) (Blaimer, Lloyd, Guillory, & Brady, 2016;McCormack, Tsai, & Faircloth, 2016;Staats et al, 2013), allowing researchers to include critical taxa in phylogenetic analyses. Lastly, more recent studies have shown the integration of existing Sanger data sets with phylogenomic data sets Leaché et al, 2014;Persons, Hosner, Meiklejohn, Braun, & Kimball, 2016;Richart, Hayashi, & Hedin, 2016;Zhang et al, 2016), demonstrating the complementarity of these two approaches. Thus, the benefits of NGS technologies have had a profound impact on our ability to resolve some of the most challenging nodes in the Tree of Life, although phylogenetic inference for many lineages dominated by nonmodel organisms has yet to benefit from NGS approaches.…”
Section: Introductionmentioning
confidence: 97%